A modified trait‐based framework for assessing the resilience of ecosystem services provided by coral reef communities. Issue 5 (3rd May 2018) - Carturan, Bruno S.; Parrott, Lael; Pither, Jason
Abstract: Climate change and other anthropogenic disturbances are having dramatic impacts on tropical coral reefs and the ecosystem services they provide. Anticipating change in ecosystem services is a pressing challenge that requires understanding how species respond to an environmental change, and how they contribute to ecosystem services. Building on analogous efforts by plant ecologists, we propose a trait‐based framework that aims to predict the resistance and recovery of coral ecosystem services against both pulse and press disturbances. The framework involves identifying effect, resistance, and recovery traits across coral species and using these to ascertain how species might (1) contribute to a service, (2) resist disturbance, and (3) recover after the disturbance. By identifying trait functional overlaps and quantifying correlations among the trait types, the framework can yield a better understanding of the potential mechanistic links between community assembly, ecosystem dynamics, and ecosystem functioning. We demonstrate the utility of the framework by applying it to a virtual scenario, implemented via simulation, in which habitat provisioning is the focal ecosystem service, and cyclones and bleaching events are the disturbances of interest. This demonstration required us to assemble an extensive dataset of relevant traits—a process that revealed key gaps in the coral trait database and in our understanding of coral functional ecology. The framework can provide predictive power for the resilience of ecosystem services and can also help identify crucial knowledge gaps, research objectives, and strategies for applying a trait‐based approach to advancing coral reef science and conservation.